The Social Construction of a Concept—Orthorexia Nervosa: Morality Narratives and Psycho-Politics. (June 2020) - Fixsen, Alison; Cheshire, Anna; Berry, Michelle
Our article explores orthorexia nervosa (ON)—an extreme fixation with healthy eating—from a social construction perspective. Interviews with people self-identified as "obsessed" with healthy eating or having ON ("Identifiers") and nonmedical professionals working with ON ("Professionals") were comparatively analyzed, along with orthorexia threads from an eating disorder website ("Posters"). Participants made sense of and rationalized their attitudes and feelings concerning healthy eating and aligned themselves according to their interests. Identifiers and Posters applauded "healthy eating" and regarded consumption of "impure" foods as leading to ill-health. Some framed their dietary discipline within an ethically motivated lifestyle, while others were preoccupied with appearance or weight management. Professionals expressed concern for, and disapproval of, extreme views and behaviors in clients and parental and social influences supporting them. Debates surrounding orthorexic practices are tangled; some individuals need help, yet dangers lie in over medicalizing or "troubling" what may be a preferred lifestyle.